Role of Zamzam water as a vital mineral supplement in the treatment of opioid dependence and tolerance: A Review - Mohd Ekhwan, Toriman; Nasir, Mohamad; Nor Hidayah, Abu Bakar (2016)
Opioid dependency or tolerance is a worldwide problem that affects all societies in terms of health, social and economic welfare. It is a need to explore more alternative treatment to address opiate dependence and tolerance besides our current conventional medication. In exploring the alternative supplement to reduce opiate dependence and tolerance, this article reviews and describes the evidence of a relationship between mineral and opiate dependence and tolerance. We also discuss about the action mechanism of mineral to alleviate opiate dependence and tolerance which are abundantly available in the Holy Zamzam water.